An Analysis of the Ventilation Efficiency of Various Configurations of Inlet and Outlet Vents in a Residential Building by CFD Simulation - Daeung Danny Kim; Hyejin Kim; Woong Seog Yim; Taesub Lim (Buildings)
Residential buildings in South Korea have equipped an energy recovery ventilation (ERV) system to improve energy efficiency as well as dilute indoor air pollution. While most studies have focused on the efficiency of energy exchange or the ventilation performance of the ERV itself, the ventilation performance can be improved by the proper location of inlet and outlet vents. For the present study, the ventilation performance of the inlet and outlet vents of the ERV was investigated by using CFD simulation. By varying the locations of inlet and outlet vents, the airflow distributions and the age of air were assessed. In addition, the air exchange effectiveness was analyzed by using the mean age of air quantitatively. As a result, a higher age of air was observed when inlet vents were moved to the center of the plan along the wall and an additional inlet or outlet vent was installed in the kitchen. In addition, the highest air exchange effectiveness was obtained when the inlet vents were located in the center of the plan along the wall. Considering the economic perspective, it is recommended to locate the inlet vents in the center to at least improve the ventilation performance.